Adverse Selection and Generosity of Alcohol Treatment Benefits - Katherine M. Harris; Roland Sturm (SAGE Publishing, 2002)
Concerns about attracting disproportionate numbers of employees with alcohol problems limit employers' willingness to offer health plans with generous alcohol treatment benefits. This paper analyzes two potential avenues of adverse selection, namely biased enrollment into plans and biased exit from plans offered by 57 employers between 1991 and 1997. We compare alcohol treatment use rates and costs of new and old enrollees between more generous and less generous plans; we also analyze disenrollment rates and enrollment duration by plan generosity for users and nonusers of alcohol treatment services. To avoid confounding benefit generosity with other plan features, in particular the use of managed care mechanisms, we compare plans that were administered in the same way by a large managed behavioral health care organization. Overall, we find no evidence of adverse selection into more generous plans. Contrary to the selection hypothesis, treatment costs of new members compared to old members are lower in firms with more generous treatment benefits than in firms with more limited benefits. Also, users of alcohol treatment services do not remain disproportionately enrolled longer in plans with generous benefits.